Logics for Studying Higher Education in Nursing: A Graduate Nurses Perspective in Pakistan - Ghulam Mustafa Rajputi Parveen Azam Ali (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2015)
Objective; This study was done to explore the logics that strive graduate nurses to higher education in nursing in Pakistan. Study design:Across section survey. Material & Methods: A self administered, five point likert scale was developed to assess the various logical reasons of enrolled graduated nurses for higher education in nursing from four nursing institutes. Data was collected from them & assessed. Results: Among the identified factors it includes 60(100%) educational factors, 54(90%) Organiza-tional factors, 51(85%) Institutional factors. Conclusion: The Main logics that lead graduate nurses for higher education are multi factorial:, it includes the gain of core practical and theoretical knowledge, organizational support for paid salaries throughout training and the institutional factors: having proper affiliation, international standards, proper hierarchy of nursing leadership are recognized as the important factors ofmotivation. Keywords: Logical , Factors, Graduate nurses, Higher education , Nursing